Microcontroller-Based Intravenous Fluid Monitoring System Design - Phisca Aditya Rosyady; Nurina Umy Habibah; Ahmad Raditya Cahya Baswara; Nuni Ihsana; Dedik Sulistiawan; Widya Rahayu Dinata (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Intravenous fluids are used to replace the body's fluid and electrolyte balance. This is a crucial need for a patient during treatment, so infusion replacement should not be delayed as it can be fatal to the patient. Medical personnel must always pay attention to the patient's infusion. This has always been a problem because the limited number of medical personnel and the large number of patients often make it difficult for medical personnel to carry out their duties. The development of technology increases human creativity and creates various tools to help humans be more effective, including in dealing with problems in the medical world. Based on this background, the author designed an infusion fluid monitoring system to facilitate nurses in hospitals that lack electrical support and internet networks. This research aims to make an intravenous fluid monitoring tool using a microcontroller effectively and realtime. The research method we use is research and development, while the data analysis method uses comparative quantitative analysis. This research consists of three main parts, namely system input, microcontroller as system processor, and system output as expected. This infusion fluid monitoring uses Load Cell to measure the volume of infusion fluid, RTC module to estimate the time of infusion fluid expiration, LCD as infusion fluid status information, and buzzer as an information alarm if the infusion fluid is detected to run out. The microcontroller used in this research is Arduino Uno. The results showed that infusion fluid has the same pressure as human body fluids (isotonic). Load Cell has a mass reading accuracy value of 99.88%, the accuracy of testing the conversion of intravenous fluid measurements into milliliters of 99.49%, and the number of infusion fluid droplets per minute under normal conditions is 20, with an estimated time out for 8 hours.